Radiofrequency ablation for unresectable locally advanced pancreatic cancer: a systematic review. Issue 2 (18th April 2013) - Fegrachi, Samira; Besselink, Marc G.; van, Hjalmar C.; van, Richard; Molenaar, Izaak Quintus
Abstract Background Median survival in patients with unresectable locally advanced pancreatic cancer lies in the range of 9–15 months. Radiofrequency ablation (RFA) may prolong survival, but data on its safety and efficacy are scarce. Methods A systematic literature search was performed in PubMed, EMBASE and the Cochrane Library with the syntax '(radiofrequency OR RFA) AND (pancreas OR pancreatic)' for studies published until 1 January 2012. In addition, a search of the proceedings of conferences on pancreatic disease that took place during 2009–2011 was performed. Studies with fewer than five patients were excluded as they were considered to be case reports. The primary endpoint was survival. Secondary endpoints included morbidity and mortality. Results Five studies involving a total of 158 patients with pancreatic cancer treated with RFA fulfilled the eligibility criteria. These studies reported median survival after RFA of 3–33 months, morbidity related to RFA of 4–37%, mortality of 0–19% and overall morbidity of 10–43%. Pooling of data was not appropriate as the study populations and reported outcomes were heterogeneous. Crucial safety aspects included ensuring a maximum RFA tip temperature of < 90 °C and ensuring minimum distances between the RFA probe and surrounding structures. Conclusions Radiofrequency ablation seems to be feasible and safe when it is used with the correct temperature and at an appropriate distance from vital structures. It appears to have a positive impact on survival. Multicentre randomized trials are necessary to determine the true effect size of RFA and to minimize the impacts of selection and publication biases.